TİP-2 BULANIK MANTIK SİSTEMLERİN BENZETİMİ İÇİN YAZILIM GELİŞTİRME - BULUT, MÜZEYYEN (Fırat Üniveristesi, 2004)
Tip-2 bulanık küme kavramı, ilk olarak klasik (tip- 1 ) bulanık kümelerin bir uzantısı olarak sunulmuştur. Tip-2 bulanık kümeler, bir bulanık küme için tam bir üyelik fonksiyonunun belirlenemediği durumlarda oldukça kullanışlıdır; dolayısıyla, bu kümeler, belirsizliklerin üstesinden gelmede çok etkindir. Ancak, tip-2 bulanık kümeleri anlamak ve kullanmak tip-1 bulanık kümelerden daha zordur. Bu zorluklara rağmen, tip-2 bulanık kümeler bir çok konuda uygulama alanı bulmuştur. Şu anda, Tip-1 bulanık mantık sistemlerin benzetiminin kolayca yapıldığı MATLAB/SIMULINK 'in 'Fuzzy Logic Toolbox'i gibi bazı ticari yazılım programları bulunmasına karşın tip-2 bulanık mantık sistemlerin benzetimi için böyle bir ticari yazılım mevcut değildir. Bu nedenle, bu tez çalışmasında MATLAB programlama dilinde yazılmış, MATLAB ve SIMULUNK 'de doğrudan tip-2 bulanık mantık uygulamalarının yapılacağı, yeni bir 'Type-2 Fuzzy Logic Toolbox' tasarlanmıştır. Ayrıca SIMULINK'de kullanmak amacıyla 'Type-2 Fuzzy Logic Controller Block' da hazırlanmıştır. Genel tip-2 bulanık mantık sistemler çok karmaşık olmaları nedeniyle uygulamalarda tercih edilmemişlerdir. Bu nedenle, sunulan 'Type-2 Fuzzy Logic Toolbox' da sadece aralıklı tip-2 bulanık mantık sistemler dikkate alınmıştır. Geliştirilen yazılım paketindeki tüm menüler, 'MATLAB-Fuzzy Logic Toolbox' ınki ile aynı formattadır ve uluslar arası kullanım için İngilizce olarak hazırlanmıştır. Anahtar Kelimeler : Tip-2 bulanık mantık, tip-2 bulanık kümeler, aralıklı kümeler, tip- 2 bulanık mantık alet kutusu.

The concept of type-2 fuzzy set was initially proposed as an extension of classical (type-1) fuzzy sets. Type-2 fuzzy sets are very useful in circumstances where it is difficult to determine an exact membership function for a fuzzy set; hence they are very effective for dealing with uncertainties. However, type-2 fuzzy sets are more difficult to use and understand than type-1 fuzzy sets. Even in the face of these difficulties, type-2 fuzzy logic has found applications in many fields. Currently, there are some commercial software programs like Fuzzy Logic Toolbox of MATLAB/SEVIULINK in which the simulation of type-1 fuzzy logic systems can be done easily but, there is no such a commercial software program for the simulation of type-2 fuzzy logic systems. Therefore, in this thesis, a new Type-2 Fuzzy Logic Toolbox written in MATLAB programming language is designed for direct applications of type-2 fuzzy logic in MATLAB and SIMULINK. Type-2 Fuzzy Logic Controller Block is also prepared for use in SIMULINK. Since general type-2 fuzzy logic systems are very complicated, they are not preferred in applications. Thus, only interval type-2 fuzzy logic systems are considered in the proposed Type-2 Fuzzy Logic Toolbox. All the menus of the developed software package are in the same format with MATLAB Fuzzy Logic Toolbox and are prepared in English for international use. Keywords: Type-2 Fuzzy Logic, type-2 fuzzy sets, interval sets, type-2 fuzzy logic toolbox.
A software development for the simulation of type-2 fuzzy logic systems
Keywords: Elektrik ve Elektronik Mühendisliği; Electrical and Electronics Engineering